PENGEMBANGAN APLIKASI SELEKSI KELAYAKAN PENGAJUAN PROPOSAL PROPOSAL SKRIPSI DAN SIDANG SKRIPSI BERBASIS WEB DI FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS BALE BANDUNG - COMPUTING INFORMATIKA; Yudi Herdiana (COMPUTING | Jurnal Informatika, 2021)
This thesis is motivated by the problems that exist at Bale University, Bandung, especially at the Faculty of Information Technology, namely the registration of thesis proposal hearings and thesis trials whose implementation is still using the manual method, even though they already have an Academic Information System (SIAKAD) application but do not include thesis registration. The purpose of this research is to create a website-based Thesis registration application in order to assist the Head of Study Program at the Faculty of Information Technology UNIBBA in selecting the feasibility of submitting a thesis proposal and thesis trial and assisting students in collecting thesis requirements, especially at the Information Technology Faculty, Bale University, Bandung. The method used is SDLC (Software Development Life Cycle) Waterfall model, using UML (Unified Modeling Language) modeling to design application designs, and using Black Box Testing methodology for application testing. The result of this research is the Development of a Web-Based Thesis Proposal Application Development at the Faculty of Information Technology, Bale University Bandung, this application was created to assist students in the thesis registration process, and the Faculty of Information Technology, Bale University Bandung in managing thesis registration files. The conclusion is that this application was successfully developed using the PHP programming language and using the Waterfall model SDLC (Software Development Life Cycle).